The value of the MIND diet in the primary and secondary prevention of hypertension: A cross-sectional and longitudinal cohort study from NHANES analysis - Song, Yanjun; Chang, Zhen'ge; Cui, Kongyong; Song, Chenxi; Cai, Zhongxing; Shi, Boqun; Dong, Qiuting; Dou, Kefei (Frontiers in Nutrition, 2023)
Background: the Mediterranean- Dietary Approaches to Stop Hypertension for neurodegenerative delay (MIND) has been regarded as a novel healthy dietary pattern with huge benefits. However, its value in preventing and treating hypertension has not been investigated. The objective of this study is to investigate the impact of adhering to the MIND diet on the prevalence of hypertension in the entire population and long-term mortality in hypertensive patients. Methods: In this prospective study, 6887 participants consisting of 2984 hypertensive patients in the National Health and Nutritional Examination Surveys were analyzed and divided into 3 groups according to the MIND diet scores (MDS; groups of MDS-low [<7.5], MDS-medium [7.5–8.0] and MDS-high [≥8.5]). The primary outcome was all-cause death and the secondary outcome was cardiovascular (CV) death. Hypertensive patients received a follow-up with a mean time of 9.25 years (median time: 111.1 months, range 2 to 120 months). Multivariate logistics regression models and Cox proportional hazards models were applicated to estimate the association between MDS and outcomes. Restricted cubic spline (RCS) was used to estimate the dose-response relationship. Results: Compared with the MDS-low group, participants in the MDS-high group presented a significantly lower prevalence of hypertension (odds ratio [OR] 0.76, 95% confidence interval [CI] 0.58, 0.97, P = 0.040) and decreased levels of systolic blood pressure (β = -0.41, P = 0.033). Among hypertensive patients, 787 (26.4%) all-cause death consisting of 293 (9.8%) CV deaths were recorded during a 10-year follow-up. Hypertensive patients in the MDS-high group presented a significantly lower prevalence of ASCVD (OR = 0.71, 95% CI, 0.51, 0.97, P = 0.043), and lower risk of all-cause death (hazard ratio [HR] = 0.69, 95% CI, 0.58, 0.81, P < 0.001) and CV death (HR = 0.62, 95% CI, 0.46, 0.85, P for trend = 0.001) when compared with those in the MDS-low group. Conclusions: For the first time, this study revealed the values of the MIND diet in the primary and secondary prevention of hypertension, suggesting the MIND diet as a novel anti-hypertensive dietary pattern.